Notes and corrections to Guerrieri & Gahari’s (2018) list of Iranian Encyrtidae (Hymenoptera, Chalcidoidea) (Zootaxa, 4444 (3)) - Fallahzadeh, Majid; Japoshvili, George; Guerrieri, Emilio (Zootaxa, 2018)
A correction to an oversight in a recently published checklist of Iranian species of Encyrtidae (Hymenoptera, Chalcidoidea) is presented, along with recommended amendments, resulting in 173 species belonging to 51 genera.